The Modern Tendencies of Bank Crediting in Ukraine - Glushchenko Victor V.; Sadova Hanna O. (Bìznes Inform, 2018)
The article defines dynamics of bank crediting of individuals and legal entities for the period of 2013–2017. The article is aimed at defining and substantiating the reasons of the newest tendencies in bank crediting. The credits granted to individuals in various aspects, namely: on the target directions, mortgage credits on terms of repayment are considered. The credits granted to non-financial corporations are analyzed in the following sections: by maturity, by size of enterprises. The percentage of credits granted to individuals and legal entities is also analyzed. The current status of bank crediting is characterized by increase of volumes due to improvement of financial condition of households and favorable macro-economic conditions. The reduction of volumes occurs only in the sphere of mortgage crediting. Among the problems of crediting can be called concealment of real incomes of individuals and inability of banks to correctly assess the credit risk of borrowers – legal entities which is caused by lack of transparent reporting and a low level of centralized tracking of credit histories of organizations.